Um punhal pútrido: uma análise da Crônica da casa assassinada de Lúcio Cardoso - Melere, Elis Regina (2018)
This work studies Crônica da casa assassinada (1959) considered Lúcio Cardoso’s masterpiece, investigating about the thematic bias of homosexuality the characters Timóteo and Maria Sinhá and from the perspective of the transgression the characters Nina and Ana, with the intention of expanding the research on the aforementioned book and, consequently, demonstrate the importance and relevance of this novel for literary studies. In order to approach the question of homosexuality, studies are presented and discussed on some of its aspects and on some romanesque figurations of the homosexual in the Brazilian literature until arriving at Maria Sinhá and Timóteo. In order to highlight and discuss the transgression in the novel, some concepts about incest, betrayal and the feminine condition in Brazilian society are analyzed, and focusing in Nina and Ana, whose actions violate the rules of patriarchal logic, metaphorically rising a dagger that exposes all the decomposition present in the Meneses family. For the understanding of homosexuality and transgression highlighted in Chronicle of the murdered house, the theoretical framework is based on Gilberto Freyre (2003); Michel Foucault (1984); Judith Butler (2008); Ruth Silviano Brandão (2006); Heleieth Saffioti (1976); Roberto Reis (1984) among others. It is evident in this contemporary themes, intriguing and disgusting work of Lúcio Cardoso flawed characters within a collapsed society - a clear demonstration that it is a novel full of conjecture and darkness that does not fear putting into play the most putrid aspects of a family moral and financially decadent.